Potential theranostic and multimodal iron oxide nanoparticles decorated with rhenium–bipyridine and –phenanthroline complexes1. Issue 21 (7th June 2015) - Carron, Sophie; Bloemen, Maarten; Vander Elst, Luce; Laurent, Sophie; Verbiest, Thierry; Parac-Vogt, Tatjana N.
<x xml:space="preserve">Abstract</x> Two structurally similar nanoparticles were designed for multimodal imaging and possible radiotherapy.